Development Of Pop Up Book Media As IPS Learning Media Material Of Cultural Diversity In North Sumatra Grade Iv Elementary School Students - Ayu Sahara; Beta Rapita Silalahi (Jurnal Pendidikan LLDIKTI Wilayah 1 (JUDIK), 2021)
This study aims to: (1) produce Pop Up Book learning media on Cultural Diversity materials in North Sumatra grade IV elementary students, (2) know the feasibility of Pop Up Book learning media on Cultural Diversity materials in North Sumatra grade IV elementary students from the validation of eligibility by material experts and media experts. This research is a type of research and development with reference to the 4D model developed by Thiagarajan (1974). Furthermore, the model is adapted into 3 stages, namely: (1) Define, (2) Design, (3) Development (Develop). The instrument used to collect data is a questionnaire. Data analysis techniques are descriptive qualitative. The media developed is validated by one material expert and one media expert. Validation by media experts is carried out 2 stages and produces a product in the form of Pop Up Book media that is eligible for grade IV elementary students. . Validation by media experts is carried out 2 stages and produces a product in the form of Pop Up Book media that is eligible for grade IV elementary students. Thus the learning media developed is considered worthy of use in learning.